Biology of PEST‐Containing Nuclear Protein: A Potential Molecular Target for Cancer Research - Khan, Nazeer Hussain; Chen, Hao-Jie; Fan, Yuanyuan; Surfaraz, Muhammad; Ahammad, MD.Faysal; Qin, Yang-Zhe; Shahid, Muhammad; Virk, Razia; Jiang, Enshe; Wu, Dong-Dong; Ji, Xin-Ying (Frontiers in Oncology, 2022)
PEST-containing nuclear protein (PCNP), a novel nuclear protein, is involved in a vital cell function of proliferation and mediates tumorigenesis. In previous preclinical studies, PCNP expression has been detected in different human cancers like neuroblastoma, lung adenocarcinoma and ovarian cancer. Current understanding bout PCNP reveals that by interacting with cell cycle regulatory proteins: tumor suppressors (p53 and pRB) and promoters (cyclin E and cyclin D), control the fate of tissue either to facilitate the process of apoptosis or cell proliferation. Key signalling pathways (PI3K/AKT/mTOR, STAT3/5 Wnt) explored in mentioned studies reveals the mechanism of actions and confirmed the PCNP participation in cell cycle regulation. Furthermore, its unique properties like ubiquitination by NIRF, co-localization in nucleus with NIRF attract the attention of researcher’s community. Aim of the current communication is to present an update on PCNP research and highlight it as potential molecular target in cancer biology with future prospective in this field. Considering the available evidence as base line of our statement, we anticipated that coming days new research insights will strengthen the aim to develop PCNP based diagnostic and therapeutic approaches that will move the PCNP from laboratory to the cancer clinic.